Concentration Level Differences between Athletes of Body Contact and Non-Body Contact Sports - Tache, Nisrina; Lubis, Leonardo; Saputra, Lucky (Althea Medical Journal, 2017)
Background: Concentration is one of the components of cognitive function, which is important for athletes in all sport branches. Every branch of sports has their own different characteristics, body contact or non-body contact, seen from the aspects of game activity that have direct or indirect physical contact, rules of the sports, behavior of the athlete and psychological demands. Basically, both sports branches need good level of concentration in order to display their best performance. The study aimed to determine the difference of concentration level between athletes of body contact and non-body contact sports. Methods: This study was an analytic observational study with cross-sectional design, conducted in the Indonesian National Sport Committee (Komite Olahraga Nasional Indonesia, KONI) Secretary Office in September 2015. Primary data were taken using the instrumental concentration test namely Grid Concentration Test. One hundred ninety three athletes were obtained and grouped in body contact (111 athletes) and non-body contact sports (82 athletes). Statistical analysis was performed using the non-parametric test of Mann-Whitney.Results: The result showed that the difference in the athleteâs concentration level between body contact and non-body contact sports was not significant (p=0.151). Nevertheless, the data collection of this study showed that body contact sports had a better concentration level than non-body contact sports however the data was not statistically significant.Conclusions: There is no significant difference in concentration level between athletes of body contact and non-body contact sports. Â